Influence of activation/deactivation process on surface-initiated atom transfer radical polymerization: An in silico investigation - Zhongyan Zhang; Hui Li; Yuqi Guo; Yao-Hong Xue; Hong Liu (Giant, 2025)
We propose a simulation approach to explore surface-initiated atom transfer radical polymerization (SI-ATRP), in which how the chain growth is affected by activation/deactivation process could be considered explicitly. Our findings indicate that these activation and deactivation mechanisms provide all polymer chains with equal growth opportunities. This process leads to a significant increase of grafting density while concurrently reducing the dispersity of the grafted chains. The ratio of activated and dormant chains is theoretically proved to eventually reach equilibrated within the activation/deactivation process. The shorter lifetime of activation/deactivation cycle leads to an even equal opportunity and a faster “stop-continue” pace for the growth of all chains. Our study is helpful for better understanding the role of activation/deactivation process in SI-ATRP from a microscopic perspective.